Association of remnant cholesterol with coronary artery ectasia: a cross-sectional study - Jing Mu; Yihan Weng; Jiquan Xiao; Yusi Huang; Xiang He; Zhixin Xie; Huimin Yu (Lipids in Health and Disease, 2024)
Abstract Objective Coronary artery ectasia (CAE) is a condition characterized by the localized or widespread dilation of one or more coronary arteries. The majority of CAE patients do not present with clinical symptoms, and the exact cause of CAE remains unclear. Therefore, a retrospective analysis was conducted to explore the potential causes of CAE. Methods This study was a retrospective analysis of patients who underwent coronary angiography at Guangdong Provincial People’s Hospital between January 2017 and July 2022, of whom 679 patients were ultimately enrolled in the study. Among them, 260 patients were diagnosed with CAE, whereas 419 patients with normal coronary results composed the control group. Remnant cholesterol (RC) was calculated as total cholesterol (TC) minus high-density lipoprotein cholesterol (HDL-C) minus low-density lipoprotein cholesterol (LDL-C). The association between RC levels and the risk of CAE was assessed via multivariable logistic models. Results Out of the 679 patients who participated in this study, with an average age of 59.9 years, 38.3% were diagnosed with CAE. Patients with CAE had higher RC levels than did those without CAE (P = 0.001). A significant positive association was observed between RC levels and the risk of CAE, with a multivariable adjusted odds ratio (OR) of 1.950 (95% confidence interval [CI]: 1.163–3.270). There was a significant positive association between RC levels and the risk of CAE in both single-vessel and multivessel dilation cases, as well as in isolated CAE and dilation secondary to coronary atherosclerosis. According to the subgroup analyses, RC levels were positively associated with the risk of CAE in participants with hypertension (OR, 1.065; 95% CI, 1.034–1.098). Conclusion RC levels are positively correlated with CAE, implying that a focus on RC could be beneficial in CAE research.